Transport Planning and Mobility in Urban East Africa (Taylor & Francis, 2021)
This book critically explores the relationship between mobility patterns, transport provision and urban development in East African cities. Bringing together contributions on the futures of mobility in urban East Africa, the chapters examine transport provision, mobility patterns, location-specific modes of transport and transformative factors for transport and mobility in the rapidly urbanising region. The book outlines different mobility needs to be addressed in transport planning to serve and shape the respective cities and examines the decision-making process in transport planning and the level of accountability to the public. The contributors show the dialectic between innovation in transport/mobility and urban development under rapid urbanisation and discusses how to practically integrate mobility and transport provision into urban development. This book will be of interest to scholars in urban planning, transport planning, transport geography, social sciences and African studies.
English
Keywords: Human geography; Politics & government; Transport: general interest; African cities, Kampala, Kenya, Mobility patterns, sustainable cites